Solid waste collection routes optimization via GIS techniques in Ipoh city, Malaysia - Malakahmad, A. (Elsevier Ltd, 2014)
Waste collection becomes more complex in developing countries in terms oflogistic, fuel and labor cost and air pollutantsemission. In this study, solid waste collection routes optimizationusing Geographical Information System (GISArcView) was investigated. Five routes were selected in different area of Ipoh city for pilot study and the present routes were optimized to reduce the length of the routes and consequently the time taken to complete the collection. Results indicate up to 22 length minimization in the routes. The collection duration was also reduced from 6934s to 4602 s. Â© 2014 The Authors. Published by Elsevier Ltd.